Use of ionic liquid in leaching process of brass wastes for copper and zinc recovery - Kilicarslan, Ayfer; Saridede, Muhlis Nezihi; Stopic, Srecko; Friedrich, Bernd (SPRINGER, 2014)
Brass ash from the industrial brass manufacturer in Turkey was leached using the solutions of ionic liquid (IL) 1-butyl-3-methyl-imidazolium hydrogen sulfate ([bmim]HSO4) at ambient pressure in the presence of hydrogen peroxide (H2O2) and potassium peroxymonosulfate (oxone) as the oxidants. Parameters affecting leaching efficiency, such as dissolution time, IL concentration, and oxidizing agent addition, were investigated. The results show that [bmim]HSO4 is an efficient IL for the brass ash leaching, providing the dissolution efficiencies of 99% for Zn and 24.82% for Cu at a concentration of 50vol% [bmim]HSO4 in the aqueous solution without any oxidant. However, more than 99% of zinc and 82% of copper are leached by the addition of 50vol% H2O2 to the [bmim]HSO4 solution. Nevertheless, the oxone does not show the promising oxidant behavior in leaching using [bmim]HSO4.
Keywords: leaching; recovery; copper; zinc; ionic liquids; oxidants; EXTRACTION; MIXTURES; REMOVAL; GOLD; Materials Science; Metallurgy & Metallurgical Engineering; Mining & Mineral Processing